An Analysis on Translation Technique and Translation Quality of Medical Terms in an Article Entitled "Critical Illness due to 2009 A/H1N1 Influenza in Pregnant and Postpartum Women: Population Based Cohort Study Produced by Google Translate - Ika Oktaria Cahyaningrum (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The purposes of this research are to describe the translation technique used by Google Translate in translating English medical terms in an article entitled Critical Illness Due To 2009 A/H1n1 Influenza in Pregnant and Postpartum Women: Population Based Cohort Study and to know the translation quality in terms of accuracy and acceptability. This research used purposive sampling technique to select the data. Two methods were used to collect the data; content analysis was obtained to collect the first data from source text and target text and interview and close and open ended questionnaire was obtained to gather data of the accuracy and acceptability. The findings of the research are as follow: there are five techniques to translate English medical terms literal translation, borrowing includes naturalized borrowing and pure borrowing, calque, transposition, and amplification.